Penguasaan Peraturan Pertandingan dan Keyakinan Diri: Bagaimana Pengaruhnya Terhadap Pengambilan Keputusan Wasit Tenis Lapangan? - Zikri Muthahari; Damrah Damrah; Deby Tri Mario (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the influence of match-rule mastery and self-confidence on the decision-making of tennis umpires. A quantitative approach with a correlational design was used to objectively analyze the relationships and influences among variables. A total of 30 tennis umpires affiliated with the PELTI Refereeing Committee of West Sumatra Province participated in this study. Data were collected using three questionnaires whose validity and reliability had been tested (α=0.925–0.944). Data were analyzed using descriptive statistics, normality and linearity tests, and Pearson correlation and linear regression analyses at a significance level of 0.05. The results showed that match-rule mastery (M=80.00±2.77) and self-confidence (M=82.57±3.04) were in the good to very good category, while decision-making ability (M=78.27±2.96) was categorized as good. Partially, match-rule mastery had a significant effect on decision-making of 56.20% (R²=0.562; p=0.001), and self-confidence contributed 40.50% (R²=0.405; p=0.000). Simultaneously, the two variables contributed 64.20% (R²=0.642; p=0.000). These findings confirm that the higher the umpires' mastery of match rules and self-confidence, the better their ability to make decisions quickly, accurately, and fairly during a match. The results of this study provide important implications for umpire coaching and training, particularly in enhancing cognitive and psychological aspects to support professional performance. Keywords: Decision-Making, Match Rules, Self-Confidence, Tennis, Umpire